Silver complexation by metallacryptates. Issue 1 (25th November 2015) - Lamberts, Kevin; Tegoni, Matteo; Jiang, Xiang; Kou, Hui-Zhong; Englert, Ulli
Abstract : We report the first complete characterization of metallycryptates encapsulating Ag(i ) cations: carboxylato ligands derived froml -proline andl -alanine chelate and bridge six Cu(ii ) centres arranged in a slightly distorted octahedral fashion. Abstract : We report the first complete characterization of metallycryptates encapsulating Ag(i ) cations: carboxylato ligands derived froml -proline andl -alanine chelate and bridge six Cu(ii ) centres arranged in a slightly distorted octahedral fashion. Eight oxygen atoms of these ligands are disposed in square-prismatic geometry and coordinate the monovalent cation. Two alternative metallacryptates based on alanine have been identified which differ with respect to aggregation: a solid in which pairs of encapsulating sites are formed competes with an infinite chain of M(i ) coordinating sites. In contrast, the individual encrypting moieties are arranged as overall neutral and isolated molecular species in the proline-based metallacryptate. This proline derivative can accomodate Ag(i ) and Na(i ) cations and form a solid solution. Susceptibility measurements confirm ferromagnetic interactions between the Cu(ii ) within the hexanuclear proline cryptate and thus underline the similarity between solids accommodating Na(i ) and Ag(i ). Spectroscopic results suggest that these metallacryptates hardly dissociate in methanol solution.